The present status of Argentinean polychrotid species of the genus Pristidactylus and description of its southernmost taxon as a new species - Cei, José (2001)
A new species of Pristidactylus from the southern Patagonian region of Argentina is described. This new species shows peculiar throat coloration in males, a secondary sex character that is unique in this genus. Different character combinations led to the revalidation of Pristidactylus araucanus from the basaltic districts of Mendoza and Neuquén, Argentina. The conservative retention of the juvenile pattern in adult females, besides other mensural characters in both sexes, indicates its specific identity relative to Pristidactylus scapulatus and Pristidactylus fasciatus. General considerations of the evolutionary history of the genus Pristidactylus are reviewed and a key to the Argentinean taxa is provided.